2016
DOI: 10.1371/journal.pone.0161264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Non-Nutritive Sweeteners on Glucose Metabolism and Appetite Regulating Hormones: Systematic Review of Observational Prospective Studies and Clinical Trials

Abstract: BackgroundThe effects of non-nutritive sweeteners (NNS) on glucose metabolism and appetite regulating hormones are not clear. There is an ongoing debate concerning NNS use and deleterious changes in metabolism.ObjectivesThe aim of this review is to analyze the scientific available evidence regarding the effects of NNS on glucose metabolism and appetite regulating hormones.Data Sources and Study Eligibility CriteriaWe identified human observational studies evaluating the relation between NNS consumption and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 47 publications
1
55
0
5
Order By: Relevance
“…Recent research indicates differential effects of sucralose, a type of NNS, on glucose metabolism between normal weight people and people with obesity [18]. A recent review examined the effects of NNSs on glucose metabolism and appetite-regulating hormones [19]. However, it mainly focused on the evidence linking NNS consumption to the risks for chronic diseases including obesity, diabetes, and metabolic syndrome rather than the short-term response of blood glucose level to NNS consumption [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research indicates differential effects of sucralose, a type of NNS, on glucose metabolism between normal weight people and people with obesity [18]. A recent review examined the effects of NNSs on glucose metabolism and appetite-regulating hormones [19]. However, it mainly focused on the evidence linking NNS consumption to the risks for chronic diseases including obesity, diabetes, and metabolic syndrome rather than the short-term response of blood glucose level to NNS consumption [19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review examined the effects of NNSs on glucose metabolism and appetite-regulating hormones [19]. However, it mainly focused on the evidence linking NNS consumption to the risks for chronic diseases including obesity, diabetes, and metabolic syndrome rather than the short-term response of blood glucose level to NNS consumption [19]. The purpose of the current study was to systematically review and quantitatively synthesize existing scientific evidence from randomized controlled trials (RCTs) on the glycemic impact of NNSs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that most NNS have little or no effect on the serum biochemical parameters of normal and diabetic human subjects (Romo‐Romo et al, ; Shankar, Suman, & Sriram, ; Tey et al, ). In the present study, it was observed that NNS influence serum antioxidant status.…”
Section: Resultsmentioning
confidence: 97%
“…[24] Given these results, the American Dietetic Association stated that non-nutritive sweeteners were safe for consumption because they do not affect the glycemic response in patients with diabetes mellitus. [25,26] …”
Section: Figure 1 Network Meta-analysis Of Six Interventions In Glycmentioning
confidence: 99%